PENGARUH MOTIVASI, KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN KOPDIT CU PARDOMUAN PAKKAT - Simangunsong, Elisabeth; Kristina, Mey Happy; Bangun, Kristina (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2025)
This study aims to test and analyze the influence of motivation, communication and work discipline on employee performance at CU Pardomuan Pakkat Cooperative. Data collection was carried out on a population of 50 employees and the number of research samples was 50 samples. The technique used was saturated sampling. Data analysis using SPSS version 25. The data analysis techniques used in this study were validity and reliability tests, multiple linear regression analysis and hypothesis testing. From the results of partial testing, each variable is, the t-value of motivation is (6.174)> t-table (1.679) with a significance level of 0.000 <0.05, so that motivation has a significant effect on employee performance. The t-value of communication is (6.989)> t-table (1.679) with a significance level of 0.000 <0.05, so that communication has a significant effect on employee performance. The t-value of work discipline of (12,890) > ttable (1.679) with a significance level of 0.000 < 0.05, so that work discipline has a significant effect on employee performance. The F test shows that motivation, communication and work discipline simultaneously have a significant effect on employee performance at CU Pardomuan Pakkat Cooperative, with an Fcount value of 20.683 > Ftable of 3.20 and a significance value of 0.000 < 0.05. The results of the study formulated that the multiple linear regression equation is KK = 7.176 + 0.268 M + 0.178 K + 0.732DK + e. This means that motivation, communication and work discipline have a significant partial effect on employee performance at CU Pardomuan Pakkat Cooperative.The determination coefficient of 0.773 is equal to 77.3%, meaning that employee performance can be explained by the variables of motivation, communication and work discipline by 77.3% while the remaining 22.7% is explained by other factors such as work stress, training and others that were not included in this study.